St. Louis Paper - The Zinc Ores of the Joplin District (with Discussion) - W. Geo. Waring (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
The winning of zinc and lead ores from the comparatively shallow deposits of the Joplin district presents few such problems for the mining engineer as are encountered in deep ore mining and in the handling of complex ores. However, for those who are interested in the origin and nature of ore deposits in general, there is much here to investigate, and upon studies in this direction will depend, in no small measure, the future of an industry that has produced during the year 1916, in southwest Missouri, lead and zinc ores to the value of $26,319,383; adding $46,022,164 to the metallic wealth of the nation. Including the adjacent mines in Ottawa County, Oklahoma, and Cherokee County, Kansas, which are really continuations of the Joplin district, the total value of ores produced reached the sum of $34,089,503, and that of the metals, $58,927,941.l The ores produced in the Joplin district are remarkable on account of their almost uniformly high metal content in both lead and zinc. Their superiority in this regard is unparalleled, and is doubtless due to certain geological conditions that are now possibly explicable, provided that the artesian circulation = ascension hypothesis of the origin of the ore deposits is proved beyond question to be the only tenable explanation of the facts. These, as well as other valuable zinc-ore deposits, are bound to be exhausted in time, for ordinary mining purposes, and it concerns the mining engineer that the conditions under which ores of this character were actually deposited in the form in which they occur, may, if possible, be ascertained, in order that he may learn where to look for similar deposits in other regions, or even how to reproduce artificially such condi-